2012
DOI: 10.1007/s11042-011-0963-2
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced encryption algorithm for video based on multiple Huffman tables

Abstract: Encryption is one of the fundamental technologies that is used in the security of multimedia data. Unlike ordinary computer applications, multimedia applications generate large amount of data that has to be processed in real time. This work investigates the problem of efficient multimedia data encryption. A scheme known as the Randomized Huffman Table scheme was recently proposed to achieve encryption along with compression. Though this scheme has several advantages it cannot overcome the chosen plaintext atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Later Zheng [3] proposed a modified signcryption technique with hash function that involves simple mathematical operations such as +,-,*,%. They have shown that their signcryption scheme reduces the computational and communication cost up to 40% compared to traditional signature then encryption [4] scheme. And also their signcryption scheme was publically verifiable but that does not provide forward secrecy.…”
Section: Survey On Existing Signcryption Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later Zheng [3] proposed a modified signcryption technique with hash function that involves simple mathematical operations such as +,-,*,%. They have shown that their signcryption scheme reduces the computational and communication cost up to 40% compared to traditional signature then encryption [4] scheme. And also their signcryption scheme was publically verifiable but that does not provide forward secrecy.…”
Section: Survey On Existing Signcryption Schemesmentioning
confidence: 99%
“…Case 1: Consider a situation where an attacker knows p a ,p b and D which are publically available and he tries to find k, in such a case solving k from (3) is computationally infeasible by the definition of HECDLP. Case 2:Consider an equation (4) in which S, p a and R arepublically available and if an attacker wants to find K2 he needs to identify private key of the receiver d b from (5) but by the definition of HECDLP solving it is computationally infeasible. (5) Case 3: Consider an equation to find S in signcryption using HECC (6), if an attacker needs to find k he has to calculate d a but finding it is computationally infeasible both from (6) and (7).…”
Section: B Confidentialitymentioning
confidence: 99%
“…A lot of lightweight algorithms for the limited resources terminals have many achievements [10,11]. But nearly all the proposed algorithms are from the perspective of protecting the entire parts of a data, without considering reducing unnecessary protections.…”
Section: Related Workmentioning
confidence: 99%
“…Authentication, integrity, and non-repudiation can be ensured through digital signature [2]- [7] and confidentiality can be assured through encryption [8]- [10] algorithms. In old mechanisms, the sender first signs the message and then encrypts them by using digital signature and encryption algorithms.…”
Section: Introductionmentioning
confidence: 99%